2003
DOI: 10.1073/pnas.1230693100
|View full text |Cite
|
Sign up to set email alerts
|

The Notch ligand Delta1 is sequentially cleaved by an ADAM protease and γ-secretase

Abstract: Notch signaling is involved in numerous cell fate decisions in invertebrates and vertebrates. The Notch receptor is a type I transmembrane (TM) protein that undergoes two proteolytic steps after ligand binding, first by an ADAM (a distintegrin and metalloprotease) in the extracellular region, followed by ␥-secretasemediated cleavage inside the TM domain. We demonstrate here that the murine ligand Delta1 (Dll1) undergoes the same sequence of cleavages, in an apparently signal-independent manner. Identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
224
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(230 citation statements)
references
References 40 publications
5
224
0
1
Order By: Relevance
“…It has been previously reported that a truncated intracellular isoform of Delta evidences prominent nuclear localization (Bland et al, 2003;Ikeuchi and Sisodia, 2003;LaVoie and Selkoe, 2003;Six et al, 2003). The intracellular domain of Delta1 results in a non-proliferating senescent-like cell phenotype that depends on the expression of the cell cycle inhibitor, p21, and is suppressed by constitutively active Notch1 (Kolev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously reported that a truncated intracellular isoform of Delta evidences prominent nuclear localization (Bland et al, 2003;Ikeuchi and Sisodia, 2003;LaVoie and Selkoe, 2003;Six et al, 2003). The intracellular domain of Delta1 results in a non-proliferating senescent-like cell phenotype that depends on the expression of the cell cycle inhibitor, p21, and is suppressed by constitutively active Notch1 (Kolev et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Delta is cleaved sequentially by the RIP mechanism probably including ADAM and gamma-secretase (Ikeuchi and Sisodia, 2003;LaVoie and Selkoe, 2003;Qi et al, 1999;Six et al, 2003), and the cleaved Dll1-IC is released from the cell membrane and translocates to the nucleus, where it suppresses notch signaling through the disruption of Notch1-IC transcriptional complex. Henceforth, the results of this study may begin to shed some light on what may be a signal cross-talk mechanism of Notch and Delta after cleavage by gamma-secretase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuzbanian and Neuralized are the central enzymes in the proteolytic and endocytosis-mediated processes, respectively, that regulate Delta expression at the cell surface (Lai et al, 2001;Mishra et al, 2002;reviewed in Le Borgne et al, 2005). Delta undergoes cleavage by Kuzbanian, resulting in shedding and clearance of the extracellular domain (Bland et al, 2003;Six et al, 2003), a process that ultimately downregulates its ligand activity. Thus, it is possible that elevated Delta levels occur where Kuzbanian expression is suppressed.…”
Section: Delta Expression and Lineage Identitymentioning
confidence: 99%
“…toma cells promote filipodia formation and process outgrowth (Franklin et al, 1999;De Joussineau et al, 2003), suggesting that Delta acts to mediate changes in neurite architecture. Furthermore, several recent studies have identified alternative mechanisms for Delta function through proteolytic and endocytosismediated processes that alter the structure and subcellular distribution of the Delta protein (Parks et al, 2000;Bland et al, 2003;LaVoie and Selkoe, 2003;Six et al, 2003). Altogether, these studies point to an additional level of activity of the Delta protein that remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%